2019
DOI: 10.1002/art.40896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary and Supplemental Omega‐3 Polyunsaturated Fatty Acids on Risk of Recurrent Gout Flares

Abstract: Objective To determine the relationship between omega‐3 polyunsaturated fatty acid (n‐3 PUFA) consumption (dietary or supplemental) and risk of gout flares. Methods We used data from the Boston University Online Gout Study, an internet‐based case‐crossover study conducted from February 2003 to January 2012. At the times of gout flares (hazard period) and during gout flare–free periods (control periods), participants completed questionnaires regarding exposures, including supplements and diet, during the preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…While L3 and L5 can mostly associate with changes in levels of lipids in the sera, since they reflect the lipid β-methylenes and α-methylenes, common to most medium and long-chain fatty acids, the L6 group reflects polyunsaturated allylic methylenes due to the presence of polyunsaturated fatty acids (PUFAs), which are known to play a central role in the homeostasis of the immune system. PUFAs have been associated with both proinflammatory (ω6-PUFAs) and anti-inflammatory (ω3-PUFAs) features 44–46…”
Section: Discussionmentioning
confidence: 99%
“…While L3 and L5 can mostly associate with changes in levels of lipids in the sera, since they reflect the lipid β-methylenes and α-methylenes, common to most medium and long-chain fatty acids, the L6 group reflects polyunsaturated allylic methylenes due to the presence of polyunsaturated fatty acids (PUFAs), which are known to play a central role in the homeostasis of the immune system. PUFAs have been associated with both proinflammatory (ω6-PUFAs) and anti-inflammatory (ω3-PUFAs) features 44–46…”
Section: Discussionmentioning
confidence: 99%
“…With respect to gout, a small case-control study on patients with this inflammatory condition showed an association between high ω-3 FA levels in the blood and lower frequency of gout attacks [23]. Additionally, ω-3 PUFA-rich fish consumption was reportedly associated with lower risk of recurrent gout attacks in a case-crossover study [24]. Moreover, the anti-inflammatory effects of ω-3 PUFAs were supported by the results obtained in animal models of acute inflammation induced by monosodium urate crystals [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that consumption of fish containing omega-3 PUFA was associated with a lower propensity of recurrent gout flares. [35,36] The exact mechanism is elucidated to be as follows: inhibition of caspase-1 activation, IL-1β secretion, inhibition of NLRP3 inflammasome activation and chemotaxis. [37] Other therapies which show promise in treating gout, but require further research include guava leaves, red ginger and cocoa.…”
Section: Teamentioning
confidence: 99%